فاعلية نموذج كولب للتعلم الخبراتي في تنمية التفكير المنتج والاستمتاع بتعلم الرياضيات لدى تلاميذ المرحلة الإعدادية - حسن، مها علي محمد Hasan, Maha Ali Mohammed (الجمعية المصرية لتربويات الرياضيات, 2024)
هدف البحث إلى التعرف على فاعلية نموذج كولب للتعلم الخبراتي في تنمية مهارات التفكير المنتج والاستمتاع بتعلم الرياضيات لدى تلاميذ الصف الثاني الإعدادي، وتكونت مجموعة البحث من مجموعتين إحداهما تجريبية والأخرى ضابطة، وتم تطبيق أدوات البحث قبليا (اختبار التفكير المنتج -مقياس الاستمتاع بتعلم الرياضيات)، ثم التدريس باستخدام نموذج كولب للتعلم الخبراتي لتلاميذ المجموعة التجريبية وتم التدريس لتلاميذ المجموعة الضابطة بالأساليب المعتادة، ثم تطبيق أدوات البحث بعديا، وتوصلت نتائج البحث إلى: وجود فروق دالة إحصائيا بين متوسطي درجات تلاميذ المجموعتين التجريبية والضابطة في كل من اختبار التفكير المنتج ومقياس الاستمتاع بتعلم الرياضيات لصالح المجموعة التجريبية، وكذلك فاعلية النموذج في تنمية مهارات التفكير المنتج والاستمتاع بتعلم الرياضيات لدى تلاميذ الصف الثاني الإعدادي، وقدم البحث عددا من التوصيات منها: تضمين نموذج كولب للتعلم الخبراتي في المناهج الدراسية لتعزيز مهارات التفكير المنتج والاستمتاع بتعلم الرياضيات لدى التلاميذ وتوفير التدريب وتقديم الدعم اللازم للمعلمين لتوظيف النموذج في تدريس الرياضيات. The research aimed to identify the effectiveness of Kolb's model of experiential learning for developing productive thinking skills and enjoyment in learning mathematics among second-year prep school pupils. The research group consisted of two groups, one experimental and the other control, and the research tools were applied pre-test (productive thinking test- enjoyment in learning mathematics scale),Then teaching using the Kolb model of experiential learning for the pupils of the experimental group was taught to the students of the control group using the usual methods, then applying the research tools laterally. The results of the research reached: There are statistically significant differences between the average scores of the pupils of the experimental and control groups in both the productive thinking test and the enjoyment in learning mathematics scale. For the benefit of the experimental group, as well as the effectiveness of the model in developing productive thinking skills and enjoyment of learning mathematics among second-year prep school pupils. The research presented a number of recommendations, including: including the Kolb model of experiential learning in the school curricula to enhance productive thinking skills and enjoyment of learning mathematics among pupils, and provide the necessary training and support For teachers to employ the model in teaching mathematices.
Keywords: الاستراتيجيات التعليمية -- مقرر الرياضيات -- تنمية مهارات التفكير -- طلبة المرحلة الإعدادية